Oral Rehabilitation After Surgical Removal of Pleomorphic Adenoma - Goiato, Marcelo Coelho [UNESP]; Tamae, Adriano Caires [UNESP]; Santos Silva, Pedro Ivo [UNESP]; Santos, Daniela Micheline dos [UNESP]; Iyda, Mariana Garib [UNESP]; Moreno, Amalia [UNESP]; Magro Filho, Osvaldo [UNESP]; Bertoz, André Pinheiro de Magalhães [UNESP] (Lippincott Williams & Wilkins, 2011)
Although tumors of minor salivary glands are rare, the pleomorphic adenoma is the most common pathology among the benign neoplasm and can be found with high prevalence in the junction between hard palate and soft palate. The treatment of choice for most of maxillary tumors is surgical through either a total or partial maxillectomy. However, surgical defects caused by such type of treatment lead to both clinical and psychologic disorders for the patient. The immediate oral rehabilitation using interim palate obturator after maxillectomy provides optimization on the healing process, recovers the stomatognathic functions after surgery, and avoids psychosocial sequelae for the patients. This clinical report aimed to present the rehabilitation with immediate palate obturator of a patient who underwent a partial maxillectomy due to a hard palate pleomorphic adenoma of minor salivary glands. We report the clinical importance of the prosthetic rehabilitation and the improvements on both quality of life and stomatognathic functions of this patient. It can be concluded that the immediate rehabilitation of the patient after partial maxillectomy by using an interim palate obturator was a great option and provided clinical benefits in the immediate postoperative period, improving the patient's quality of life, allowing the patient's reinsertion into society, and reducing the surgical treatment sequelae.
Keywords: Maxillofacial prosthesis; adenoma; oral cancer